Stigma and Mental Health during COVID-19 New Normal Transition in Indonesia - Leny Latifah; Yusi Dwi Nurcahyani; Diah Yunitawati; Marizka Khairunnisa; Cati Martiyana (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Social isolation and economic catastrophic became the main characters of the current pandemic.Historically, the strongest stigmas related to diseases were characterized as highly transmittable, potentiallylethal, and without remedy. All represented COVID-19 during the early transition into the new normal. Weaimed to analyzed stigma and economic stressors concerning mental health. Method: We conducted a crosssectionalonline survey of 1375 participants in Java, Indonesia. Mental health status evaluated with DASS-21. The presence of social and self-stigma related to Covid-19 assessed with a questionnaire developed basedon seven domains of public stigma. Demographics and other psychosocial stressors were assessed withan online questionnaire. Descriptive analyses and logistic regression had carried out. Result: A very highpercentage of perceived and anticipated self-stigma and social stigma revealed. Controlling demographicsfactors, clear self-stigma increased the risk for depression (2.323 (1.241-4.346), p<0.05), anxiety (2.134(1.205-3.777), p<0.05) and stress 3.931 (1.779-8.685), P<0.001). Clear social stigma increased the risk foranxiety (2.000 (1.066-3.756), p<0.05) but not on depression and stress.Conclusion: Ensuring basic needsfulfilment and eliminating stigma is critical for supporting mental health in the Covid-19 pandemic. Furtherresearch into the stigma-related risks is necessary because it represents an important need for interventionin public health.